Preparation method of ABO3 type perovskite catalyst for efficient catalytic oxidation of ethyl acetate
The ABO3 perovskite catalyst was prepared by sol-gel method and acetic acid etching method, which solved the problems of insufficient activity of perovskite catalysts and high cost of noble metal catalysts, and achieved the effect of efficient catalytic oxidation of ethyl acetate.
Patent Information
- Application Number
- CN202510188337.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-04-08
AI Technical Summary
The existing perovskite catalysts agglomerate during high-temperature calcination, resulting in a small specific surface area and less exposure to active centers, limiting catalytic activity, and the precious metal catalysts are costly and have low economic benefits.
ABO3 perovskite catalyst was prepared by sol-gel method and acetic acid etching method. By selectively etching the A-position element on the surface, the active center of the B-position element was exposed, and the catalytic activity was improved.
The ABO3 perovskite catalyst prepared has a conversion rate of 90% catalytic oxidation of ethyl acetate at 169°C. It has low energy consumption, good catalytic activity and stability, and has high economic benefits. It can replace precious metal catalysts.
Smart Images

Figure CN119771428A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of pollutant purification, and in particular to a method for preparing an ABO3 type perovskite catalyst for efficiently catalyzing and oxidizing ethyl acetate. Background Art
[0002] Volatile organic compounds (VOCs) participate in atmospheric photochemical reactions, which can enhance atmospheric oxidation or damage the ozone layer, and even affect water safety through processes such as sedimentation. There are many types of VOCs, which can be divided into hydrocarbons, ketones, alcohols, aldehydes, esters, and halogenated compounds based on functional groups. Ethyl acetate, as a substitute for benzene solvents, has been widely used in printing, furniture, leather and other manufacturing industries, so the amount of ethyl acetate tail gas generated has gradually increased.
[0003] At present, the main treatment method for VOCs such as ethyl acetate is catalytic oxidation, which has the characteristics of high efficiency, low energy consumption, and no secondary pollution. However, the catalyst used is mainly CAS-KR-V01 catalyst with precious metals such as Pd and Pt as active components. The cost of using this type of catalyst is relatively high, and the economic and social benefits for small and medium-sized enterprises are relatively low. Therefore, the development of new non-precious metal catalysts is crucial for the treatment of VOCs such as ethyl acetate.
[0004] Among non-precious metal catalysts, perovskite materials have attracted the attention of researchers due to their good thermal stability, stable and controllable crystal structure, and abundant active oxygen species. However, the agglomeration and sintering of perovskite oxides during high-temperature calcination result in a small specific surface area of the catalyst, and the surface of the perovskite is preferentially occupied by inert A-site elements, resulting in less exposure of active centers, which severely limits the catalytic activity. Therefore, it is urgent to obtain new non-precious metal catalysts with excellent catalytic activity. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing an ABO3 type perovskite catalyst for efficiently catalyzing and oxidizing ethyl acetate, so as to solve the problems existing in the above-mentioned prior art.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] One of the technical solutions of the present invention is a method for preparing an ABO3 type perovskite catalyst for high-efficiency catalytic oxidation of ethyl acetate, comprising the following steps:
[0008] (1) dispersing metal salt A and metal salt B in a solvent, then adding citric acid, heating and stirring to form a uniform wet sol, followed by drying, roasting, and grinding to obtain a perovskite material;
[0009] The A metal salt includes lanthanum nitrate or cerium nitrate;
[0010] The B metal salt includes cobalt nitrate or manganese nitrate;
[0011] (2) The perovskite material is etched with an acetic acid solution, washed, and dried to obtain the ABO3 type perovskite catalyst.
[0012] Furthermore, when the A metal salt is lanthanum nitrate, the B metal salt is cobalt nitrate, and the obtained perovskite material is LaCoO3;
[0013] When the A metal salt is cerium nitrate, the B metal salt is manganese nitrate, and the obtained perovskite material is CeMnO3.
[0014] Furthermore, in step (1), the usage ratio of the metal salt A, the metal salt B and the citric acid is 0.01-0.05 mol: 0.01-0.05 mol: 4.2-31.5 g.
[0015] Furthermore, in step (1), the temperature of the heating and stirring reaction is 70-90° C.; and the grinding is grinding to a particle size of 200 mesh.
[0016] Furthermore, in step (1), the drying temperature is 100 to 120° C. and the drying time is 12 to 24 hours.
[0017] Furthermore, in step (1), the calcination comprises: firstly heating the temperature to 200-250°C at a heating rate of 2°C / min and keeping the temperature for 1-4h, and then heating the temperature to 650-850°C at a heating rate of 5°C / min and keeping the temperature for 2-6h.
[0018] Furthermore, in step (1), the amount ratio of the A metal salt, the B metal salt and the citric acid is 0.03mmol:0.03mol:15.13g; the temperature of the heating and stirring reaction is 80°C; the temperature of the drying is 120°C and the time is 12h; the calcination includes: first heating to 200°C at a heating rate of 2°C / min and keeping warm for 1h, then heating to 750°C at a heating rate of 5°C / min and keeping warm for 2h.
[0019] Furthermore, in step (2), the concentration of the acetic acid solution is 1 to 7 mol / L, and the etching time is 30 to 240 min.
[0020] Furthermore, in step (2), the drying temperature is 60 to 80° C. and the drying time is 6 to 12 hours.
[0021] Furthermore, in step (2), the concentration of the acetic acid solution is 5 mol / L, and the etching time is 30 min; the drying temperature is 60° C., and the drying time is 12 h.
[0022] The second technical solution of the present invention: an ABO3 type perovskite catalyst prepared by the above preparation method.
[0023] The third technical solution of the present invention: an application of the above-mentioned ABO3 type perovskite catalyst in the catalytic oxidation of ethyl acetate.
[0024] Furthermore, the temperature of the catalytic oxidation is 100-200°C.
[0025] Furthermore, the application method includes: filling the ABO3 type perovskite catalyst in a quartz tube (with a specification of 6×9 mm), and then introducing ethyl acetate gas to perform a catalytic oxidation reaction.
[0026] The present invention discloses the following technical effects:
[0027] (1) The ABO3 type perovskite catalyst prepared by the present invention has a conversion rate of 90% in catalytic oxidation of ethyl acetate at 169°C, and has the advantages of low energy consumption, good catalytic activity, good stability, etc. At the same time, the preparation process of the ABO3 type perovskite catalyst of the present invention is simple (prepared by a simple sol-gel method combined with an etching method), and has high economic benefits, which solves the problems of low catalytic energy efficiency of existing perovskite catalysts and high cost of commercial catalysts.
[0028] (2) The ABO3 perovskite catalyst prepared by the present invention is a potential application material that can replace precious metal catalysts and has great potential in subsequent market promotion.
[0029] (3) The etching method of the present invention can selectively etch the A-site elements (such as La or Ce) on the surface of LaCoO3 and CeMnO3 perovskite materials, effectively regulating the surface structure of the perovskite materials, exposing the B-site elements (such as Co or Mn) at the catalytic active sites, enhancing the reducibility of the catalyst, and thereby improving the catalytic oxidation effect of ethyl acetate. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 XRD diagrams of the catalysts prepared in Examples 1 to 4 and Comparative Example 1 of the present invention;
[0032] Figure 2 The SEM images of the catalysts prepared in Example 1 and Comparative Example 1 of the present invention, wherein A is Example 1 and B is Comparative Example 1;
[0033] Figure 3 The XPS graphs of the catalysts prepared in Example 1 and Comparative Example 1 of the present invention;
[0034] Figure 4 H2-DPR and O2-TPD diagrams of the catalysts prepared in Example 1 and Comparative Example 1 of the present invention, wherein A is the H2-DPR diagram and B is the O2-TPD diagram;
[0035] Figure 5 The activity diagram of the catalyst prepared in Examples 1 to 4 of the present invention and Comparative Example 1 for catalytic oxidation of ethyl acetate;
[0036] Figure 6 The activity diagram of the catalyst prepared in Example 1 and Example 6 of the present invention for catalytic oxidation of ethyl acetate;
[0037] Figure 7 The activity diagram of the catalyst prepared in Example 1 of the present invention and Comparative Example 3 for catalytic oxidation of ethyl acetate;
[0038] Figure 8 The activity diagram of the catalyst prepared in Example 1, Example 7 and Comparative Example 4 of the present invention for catalytic oxidation of ethyl acetate;
[0039] Fig. 9 This is a cycle performance diagram of catalytic oxidation of ethyl acetate by the catalyst prepared in Example 1 of the present invention;
[0040] Fig.10 This is a long-term stability diagram of the catalyst prepared in Example 1 of the present invention for catalytic oxidation of ethyl acetate;
[0041] Fig.11 This is the activity diagram of the catalyst prepared in Example 1 of the present invention for catalytic oxidation of ethyl acetate or toluene. DETAILED DESCRIPTION
[0042] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0043] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0044] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0045] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0046] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0047] It should be pointed out that the matters not described in detail in the present invention are conventional operating means in the art and are not the focus of the present invention.
[0048] The “parts” described in the following examples are all “parts by weight”.
[0049] Example 1
[0050] A method for preparing an ABO3 perovskite catalyst for efficient catalytic oxidation of ethyl acetate:
[0051] (1) 12.99 g of lanthanum nitrate (0.03 mol) and 8.73 g of cobalt nitrate (0.03 mol) were added to deionized water and stirred at room temperature for 30 min to form a dispersion, and then 15.13 g of citric acid was added and heated and stirred (temperature was 80° C.) to form a uniform wet sol by complexation, which was then placed in a blast oven for drying (drying temperature was 120° C. and drying time was 12 h) to obtain a loose and porous perovskite precursor;
[0052] The perovskite precursor was loaded into an alumina crucible with a lid and placed in a muffle furnace and heated to 200°C at a heating rate of 2°C / min and calcined for 1 h, then heated to 750°C at a heating rate of 5°C / min and calcined for 2 h. After annealing, it was ground to 200 mesh to obtain LaCoO3 perovskite material.
[0053] (2) Weigh 1 g of the LaCoO3 perovskite material prepared in step (1) and disperse it in 100 mL of 5 mol / L acetic acid solution, stir (etch) at room temperature for 30 min, filter to obtain a solid residue, then wash the solid residue three times with deionized water and anhydrous ethanol respectively, and place it in a 60°C forced air oven to dry for 12 h to obtain an ABO3 type perovskite catalyst (i.e., LaCoO3 catalyst treated with acetic acid etching, denoted as LCO-5).
[0054] Example 2
[0055] The same as Example 1, except that the concentration of the acetic acid solution used in step (2) is 1 mol / L, and the prepared catalyst is denoted as LCO-1.
[0056] Example 3
[0057] The same as Example 1, except that the concentration of the acetic acid solution used in step (2) is 3 mol / L, and the prepared catalyst is recorded as LCO-3.
[0058] Example 4
[0059] The same as Example 1, except that the concentration of the acetic acid solution used in step (2) is 7 mol / L, and the prepared catalyst is denoted as LCO-7.
[0060] Example 5
[0061] The same as Example 1, except that the stirring (etching) time at room temperature in step (2) is 2 h, denoted as LCO-2 h.
[0062] Example 6
[0063] The same as Example 1, except that the calcination temperature in step (1) is: firstly heated to 200°C at a heating rate of 2°C / min and kept at that temperature for 1 h, and then heated to 850°C at a heating rate of 5°C / min and kept at that temperature for 2 h, denoted as LCO-T850.
[0064] Example 7
[0065] The same as Example 1, except that the lanthanum nitrate in step (1) is replaced by an equal mole of cerium nitrate, and the cobalt nitrate is replaced by an equal mole of manganese nitrate. The prepared catalyst is denoted as CMO-5.
[0066] Comparative Example 1
[0067] The same as Example 1, except that the concentration of the acetic acid solution used in step (2) is 0 mol / L, that is, the acetic acid solution is replaced by deionized water, and the obtained catalyst is recorded as LCO.
[0068] Comparative Example 2
[0069] Preparation method of Co3O4 catalyst:
[0070] (1) 8.73 g of cobalt nitrate (0.03 mol) was added to deionized water and stirred at room temperature for 30 min to form a dispersion. Then, 7.565 g of citric acid was added and heated and stirred (temperature was 80°C) to form a uniform wet sol. The sol was then dried in a forced air oven (drying temperature was 120°C and drying time was 12 h) to obtain a Co3O4 precursor.
[0071] (2) Weigh 1 g of the Co3O4 precursor prepared in step (1) and disperse it in 100 mL of 5 mol / L acetic acid solution, stir (etch) at room temperature for 30 min, filter to obtain a solid residue, then wash the solid residue three times with deionized water and anhydrous ethanol respectively, and place it in a 60°C forced air oven to dry for 12 h to obtain a Co3O4 catalyst (referred to as Co3O4).
[0072] Comparative Example 3
[0073] The same as Example 1, except that the acetic acid solution in step (2) is replaced by a propionic acid solution of equal concentration.
[0074] Comparative Example 4
[0075] The same as comparative example 1, except that the lanthanum nitrate in step (1) is replaced by an equal mole of cerium nitrate, and the cobalt nitrate is replaced by an equal mole of manganese nitrate. The obtained catalyst is recorded as CMO.
[0076] Effect Example 1
[0077] (1) The XRD patterns of the catalysts prepared in Examples 1 to 4 and Comparative Example 1 are shown in Figure 1 ; The SEM images of the catalysts prepared in Example 1 and Comparative Example 1 are shown in Figure 2 , Figure 2 A is Example 1, and B is Comparative Example 1.
[0078] from Figure 1 It can be seen that the crystal structures of the catalysts prepared in Examples 1 to 4 and Comparative Example 1 are all rhombohedral (JCPDS: 48-0123), without impurity phases. The (110) and (211) diffraction peaks of the catalysts prepared in Examples 1 to 4 shift to low angles, indicating that lattice defects can be generated by acetic acid etching. Combined with the SEM image, it can be seen that compared with the catalyst that has not been etched with acetic acid (prepared in Comparative Example 1), the agglomeration effect of the material can be significantly alleviated by acetic acid etching. Further analysis of the specific surface area change by BET-BJH shows that the specific surface area of Example 1 is 2.59 m 2 / g, while the specific surface area of comparative example 1 is 1.74m 2 / g,. The above results indicate that acetic acid can have a beneficial effect on the physical and chemical properties of the catalyst surface.
[0079] (2) The XPS graphs of the catalysts prepared in Example 1 and Comparative Example 1 are shown in Figure 3 ; H2-DPR and O2-TPD diagrams of the catalysts prepared in Example 1 and Comparative Example 1 are shown in Figure 4 , Figure 4 A is the H2-DPR diagram, and B is the O2-TPD diagram.
[0080] from Figure 3 It can be seen that the La element of the catalyst obtained by acetic acid etching in Example 1 is selectively dissolved, the Co element on the surface of the material is exposed, and the high-valent Co element on the surface is abundant. 3+ More conducive to CH bond adsorption. Figure 4 It can be seen that the catalyst obtained by acetic acid etching in Example 1 has low temperature reduction activity ( Figure 5 A) and faster oxygen migration rate ( Figure 5 Figure B).
[0081] Therefore, during the catalytic oxidation process, VOCs are more easily adsorbed on the surface of the material (the catalyst prepared in Example 1), and because the catalyst has good low-temperature reduction activity, the active sites on the surface of the material can undergo redox reactions with VOCs at relatively low temperatures and produce vacancies. At this time, bulk oxygen quickly migrates to the vacancies on the surface, accelerating the progress of the entire reaction.
[0082] Application Example 1
[0083] Catalytic activity test
[0084] A 6×9 mm quartz tube was filled with 90 mg of the catalyst prepared in the embodiment or comparative example for fixed bed reaction. 100 ppm ethyl acetate standard gas was supplied from a steel cylinder, with a flow rate of 150 sccm controlled by a mass flow meter, and entered the catalyst fixed bed for catalytic oxidation reaction (the catalyst fixed bed was heated by a tubular electric heating furnace, and the reaction temperature was controlled by a temperature controller). The tail gas after catalytic oxidation was discharged from the end of the quartz tube and entered into a gas chromatograph for analysis (two hydrogen flame ionization detectors were used for analysis to detect ethyl acetate and carbon dioxide, and SE-54 capillary chromatographic column and PQ filling column were used for simultaneous separation).
[0085] The activity diagram of the catalysts prepared in Examples 1 to 4 and Comparative Example 1 for catalytic oxidation of ethyl acetate is shown in Figure 5 The activity diagram of the catalyst prepared in Example 6 for catalytic oxidation of ethyl acetate is shown in Figure 6 The activity diagram of the catalyst prepared in Comparative Example 3 for catalytic oxidation of ethyl acetate is shown in Figure 7The activity diagram of the catalysts prepared in Example 7 and Comparative Example 4 for catalytic oxidation of ethyl acetate is shown in Figure 8 .
[0086] turn out:
[0087] (1) When the catalyst prepared in Example 1 is used as a catalyst for ethyl acetate, the conversion temperatures of T10, T50, and T90 are 128° C., 156° C., and 169° C., respectively. The catalytic oxidation activity of ethyl acetate is significantly improved, and the energy consumption is reduced.
[0088] (2) When the catalyst prepared in Example 2 is used as a catalyst for ethyl acetate, the conversion temperatures of T10, T50, and T90 are 144° C., 170° C., and 191° C., respectively. The conversion temperature is relatively high, but the conversion effect is still significantly higher than that of Comparative Example 1, which indicates that the catalytic oxidation performance of the samples after acetic acid etching treatment is improved to a certain extent.
[0089] (3) When the catalyst prepared in Example 3 is used as the catalyst for ethyl acetate, the conversion temperatures of T10, T50 and T90 are 135°C, 161°C and 185°C, respectively.
[0090] (4) When the catalyst prepared in Example 4 is used as the catalyst for ethyl acetate, the conversion temperatures of T10, T50 and T90 are 133°C, 160°C and 179°C respectively.
[0091] (5) When the catalyst prepared in Example 5 is used as a catalyst for ethyl acetate, the conversion temperatures of T10, T50, and T90 are 130°C, 162°C, and 179°C, respectively. Compared with Example 1, as the etching time of the perovskite material increases, the catalytic performance of the sample decreases slightly.
[0092] (6) When the catalyst prepared in Example 6 is used as a catalyst for ethyl acetate, the conversion temperatures of T10, T50, and T90 are 128°C, 162°C, and 185°C, respectively. Compared with Example 1, the catalytic performance of the sample decreases slightly with the increase of the calcination temperature.
[0093] (7) When the catalyst prepared in Example 7 is used as a catalyst for ethyl acetate, the conversion temperatures of T10, T50, and T90 are 133°C, 164°C, and 185°C, respectively, indicating that the method of the present invention is universal for ABO3 perovskite materials composed of different types of metals. However, compared with Example 1, the performance of the sample is slightly reduced.
[0094] (8) When the catalyst prepared in Comparative Example 1 is used as a catalyst for ethyl acetate, the conversion temperatures of T10, T50, and T90 are 155°C, 176°C, and 195°C, respectively.
[0095] (9) When the catalyst prepared in Comparative Example 2 is used as a catalyst for ethyl acetate, the fixed bed reaction temperature is 200° C. and the ethyl acetate conversion rate is only 5%, which is much lower than that of other embodiments and comparative examples in the present invention.
[0096] (10) When the catalyst prepared in Comparative Example 3 is used as a catalyst for ethyl acetate, the conversion temperatures of T10, T50, and T90 are 137°C, 170°C, and 198°C, respectively. This shows that etching LaCoO3 with acetic acid has an excellent effect on improving the catalytic activity of ethyl acetate.
[0097] (11) When the catalyst prepared in Comparative Example 4 was used as a catalyst for ethyl acetate, the conversion temperatures of T10 and T50 were 143°C and 179°C, respectively. Compared with the examples, the catalytic performance of the sample was significantly reduced.
[0098] Application Example 2
[0099] Stability test:
[0100] (1) The catalyst prepared in Example 1 was used to carry out three start-stop cycles to measure the cyclic stability of the catalyst in catalytic oxidation of ethyl acetate (the measurement method is the same as above). The results are shown in Fig. 9 .
[0101] from Fig. 9 It can be seen that the catalytic activity of the catalyst prepared in Example 1 for ethyl acetate does not decrease significantly after recycling.
[0102] (2) The catalyst prepared in Example 1 was used to carry out a continuous catalytic oxidation experiment of ethyl acetate (180°C, the measurement method is the same as above) to determine the long-term stability of the catalyst-catalyzed oxidation of ethyl acetate. The results are shown in FIG. Fig.10 .
[0103] from Fig.10 It can be seen that after working at 180℃ for 54h, the conversion rate of ethyl acetate remains at 98%. The above results show that the ABO3 perovskite treated with acetic acid etching has excellent catalytic activity and stability, and is suitable for the high space velocity and long aging conditions faced in industrial production. Therefore, it is a potential application material for efficient catalytic oxidation of ethyl acetate.
[0104] Application Example 3
[0105] Catalytic activity test:
[0106] A 6×9 mm quartz tube was filled with 90 mg of the catalyst prepared in Example 1 for fixed bed reaction. 100 ppm ethyl acetate or toluene standard gas was supplied from a cylinder and the flow rate was controlled at 150 sccm by a mass flow meter to enter the catalyst fixed bed for catalytic oxidation reaction. The tail gas after catalytic oxidation was discharged from the end of the quartz tube and entered the gas chromatograph for analysis. The results are shown in FIG. Fig.11 .
[0107] from Fig.11 It can be seen that when the temperature is 200°C, the conversion rate of toluene is only 70.7%, while the conversion rate of ethyl acetate is 100%, indicating that the ABO3 perovskite treated with acetic acid etching has excellent catalytic oxidation activity for ethyl acetate.
[0108] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing an ABO3 type perovskite catalyst for efficient catalytic oxidation of ethyl acetate, characterized in that: The following steps are involved: The A metal salt and the B metal salt are dispersed in a solvent, and then citric acid is added, and after heating for reaction, the mixture is dried and calcined to obtain a perovskite material; The A metal salt includes lanthanum nitrate or cerium nitrate; The B metal salt includes cobalt nitrate or manganese nitrate; The ABO3 type perovskite catalyst is obtained by etching the perovskite material with an acetic acid solution.
2. The method for preparing the ABO3 type perovskite catalyst according to claim 1, characterized in that: The usage ratio of the metal salt A, the metal salt B and the citric acid is 0.01-0.05 mol: 0.01-0.05 mol: 4.2-31.5 g.
3. The method for preparing the ABO3 type perovskite catalyst according to claim 1, characterized in that: The drying temperature is 100-120° C. and the drying time is 12-24 hours.
4. The method for preparing the ABO3 type perovskite catalyst according to claim 1, characterized in that: The calcination comprises: firstly heating the temperature to 200-250° C. at a heating rate of 2° C. / min and keeping the temperature for 1-4 hours, and then heating the temperature to 650-850° C. at a heating rate of 5° C. / min and keeping the temperature for 2-6 hours.
5. The method for preparing the ABO3 type perovskite catalyst according to claim 1, characterized in that: The concentration of the acetic acid solution is 1-7 mol / L, and the etching time is 30-240 min.
6. An ABO3 type perovskite catalyst prepared by the preparation method according to any one of claims 1 to 5.
7. Use of the ABO3 type perovskite catalyst according to claim 6 in catalytic oxidation of ethyl acetate.
8. The use according to claim 7, characterized in that: The temperature of the catalytic oxidation is 100-200°C.
Citation Information
Patent Citations
Preparation method for hierarchical pore perovskite catalyst
CN107376924A
Preparation method for efficiently improving catalytic oxidation of ethyl acetate by perovskite material
CN118681573A
Cited By
Preparation method of A-site cerium-doped double perovskite catalyst and application of A-site cerium-doped double perovskite catalyst in catalytic oxidation of toluene
CN120394033A